Law, Science, Technology: Regulatory Models and Decisions - Rodotà, Stefano (2004)
This paper discusses the complex and dynamic relationship between law, science and technology. In this regard, the author identifies three basic models that facilitate the interaction of legal intervention with science and technology. These models can be classified as legislative, judicial and technocratic. As will be seen in the text, each model has a distinctive approach, but they all share the need to adapt to the changes driven by the scientific paradigm. In this context, the importance of creating a "homeostatic" law is emphasised. That is, a law that can adapt to constant change. This law manifests itself in a flexible regulatory framework capable of adapting to the new realities promoted by scientific and technological innovation.